Implementasi Governansi Digital dalam Mewujudkan Pembangunan Masyarakat Inklusif di Kabupaten Banyumas Jawa Tengah - Ni Luh Putu Ening Permini; I Gede Angga Bujana Ariana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Inclusive community development is a crucial goal for local governments, ensuring that every citizen, without exception, has equal access and opportunity in development. In the digital era, digital governance has emerged as a strategic instrument to achieve this goal. This abstract discusses the implementation of digital governance in realizing inclusive community development in Banyumas Regency. This study uses a qualitative approach with a case study in Banyumas Regency, analyzing various digital initiatives that have been implemented, such as online public service platforms, village information systems, and digital literacy programs. The results of the study show that the implementation of digital governance in Banyumas Regency has made a significant contribution to community inclusion by increasing access to information and public services, increasing community participation, and strengthening transparency and accountability in governance. Various digital innovations have made it easier for people, including vulnerable groups and people in remote areas, to access basic services such as licensing, health, and education without geographical or time constraints. In addition, digital platforms have opened up space for people to be more active in voicing their aspirations, providing input, and participating in the policy-making process. However, challenges such as the digital divide (internet access and device ownership), varying digital literacy, and data security remain major concerns that need to be addressed to ensure equitable and sustainable inclusion.